Dinamika Kalium Tanah dan Hasil Padi Sawah (Oryza sativa L.) akibat Pemberian NPK Majemuk dan Penggenangan pada Fluvaquentic Epiaquepts - Muhammad Imam Al Mu'min; Benny Joy; Anni Yuniarti (Fakultas Pertanian Universitas Padjadjaran, 2016)
This experiment aimed to find out the effect of application NPK compound and water regulation on soil potassium and yield of rice (Oryza sativa L.) on Fluvaquentic Epiaquepts. This experiment was conducted from May to October 2015, at paddy field of Soil and Water Management, Soil Science and Land Resources Department, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang. The experiment was arranged in Randomized Block Design consisted of ten treatments and three replications.The treatment consisted of : Control, Waterlogged 5 cm; 150 kg NPK ha-1, Waterlogged 5 cm; 300 kg NPK ha-1, Waterlogged 5 cm; 450 kg NPK ha-1, Waterlogged 5 cm; 600 kg NPK ha-1, Waterlogged 5 cm; 750 kg NPK ha-1, Waterlogged; local recommendation, Intermittent irrigation each 1 day until waterlogged; 450kg NPK ha-1, Intermittent irrigation each 3 days until waterlogged; 450 kg NPK ha-1, and Intermittent irrigation each 5 days until waterlogged; 450 kg NPK ha-1. The results showed that there was effect of soil *potassium and yield of rice on Fluvaquentic Epiaquepts. The treatment of 750 kg NPK ha-1 that waterlogged 5 cm give the highest result of Total Potassium, it was around 281,95 mg.kg-1, available of Potassium was around 0,45 cmol+.kg-1 and the highest yield was 7,02 kg.square-1 or equal about 9,95 ton.ha-1. Keywords : Postassium, Inorganic Fertilizer Compound, Waterlogged, rice (Oryza sativa, L.)